Portfolio Keeping Ends to a Good Product: The Cases of Reading and Motivation - Azadeh Nemati (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2016)
Portfolio has been in use from the past in other disciplines. But there are growing bodies of research which document its importance in foreign language teaching. The current study was implemented on selecting 91 undergraduate students passing their general English course in Iran. Traditional reading program was administered for control group whereas; portfolio keeping was integrated into experimental group. The result of ANCOVA showed that portfolio keeping has a positive effect on reading ability of the students in experimental group. The better reading result is explained by this argument that a good product is justified by a good process. Furthermore, portfolio keeping increased their attitude/motivation towards learning English; especially it increased integrative motivation of the students more than instrumental and attitude.